A design methodology for jigless aerospace manufacture - Burley, Graham John (Cranfield University, 2005)
Between 10% and 40% of the overall cost of an aerostructure can be directly attributed to the cost of type specific, hard-tooling. Hence, any attempt to reduce the cost of aerostructure must eventually focus on reducing the need for type specific hard-tooling. The tooling is one of the major investments made during the development phase of an aircraft programme, accounting for more than a third of the development cost of a civil aircraft and nearly a quarter of the development cost of a military aircraft. The development phase for civil aircraft typically lasts two to four years and the tooling cost represents a multi-million pound forward investment with a long pay back period. Consequently, reducing the need for type specific hard-tooling will significantly reduce development costs and the time from concept to market. This thesis describes a new design-for-assembly JAM Methodology that reduces the need to manufacture and build with type specific hard-tooling. The Methodology was developed by identifying, utilising and developing existing design methodologies, and by identifying and applying enabling technologies. The methodologies are integrated to create a design algorithm that identifies and draws on the enabling technologies to achieve minimal hard tooling assembly concepts. Included in the methodologies is an innovative systems analysis tool. This enables the comparison of alternative assembly concepts ahead of the detail design, and the prediction and control of the total assembly error at the design stage. The first part of the thesis describes the development of the JAM Methodology and explains the function and purpose of each step. The second part of the thesis demonstrates, and tests, two slightly different forms of the Methodology in the re-engineering of an existing aerospace structure, and in the designing of a new aerospace structure. Publications relating to this research thesis include eleven authored, and co-authored, refereed conference papers, one journal article, and two EPSRC final reports.